The analysis of motivation and students learning independence in learning biology in SMAN 1 Lalan during the Covid-19 pandemic - Anggraini, Fiddaniyah (Library of Sultan Agung Islamic University, 2023)
This study aims to analyze and determine the factors that influence students' motivation and independence in learning biology in SMAN 1 Lalan during the Covid-19 pandemic. The research method used is descriptive qualitative. The subjects of this study were students of class X IPA, XI IPA, and XII IPA, and biology teachers. Data were collected by direct observation, questionnaires for students via a google form, and direct interviews with teachers and students. Data analysis was performed using Miles and Huberman's interactive analysis technique. The results showed that students' learning motivation was in the high category. Although some students have difficulty understanding the material and are sometimes sleepy due to the online learning process, students try to be enthusiastic about learning. While students' independence learning shows that students' independence in learning is also in the high category, they try to follow the online learning process. Although being able to access the internet is sometimes hampered by signals and students are still found who do not have laptops and cell phones. This shows that the factors that influence students' learning motivation and independence in online biology learning at SMAN 1 Lalan include the goals to be achieved, a sense of desire to succeed, student conditions, difficulties in accessing the internet, the role of parents, the role of teaching and learning. environmental conditions.Â Keywords: learning motivation; independent learning; online learning